2015
DOI: 10.1039/c4em00504j
|View full text |Cite
|
Sign up to set email alerts
|

Workplace exposure to airborne alumina nanoparticles associated with separation and packaging processes in a pilot factory

Abstract: Workplace exposure to airborne Al2O3 nanoparticles in a pilot factory was characterised by particle concentrations, size distribution, morphology and chemical composition, compared with background particles. Real-time variations in number concentration (NC20-1000 nm), respirable mass concentration (MC100-1000 nm), active surface area concentration (SAC10-1000 nm) and particle size were measured at production locations involved in separation and packaging activities. Measurements during stable production period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…In this study, the order of CR value at the location of slag releasing was: CR SAC (5.39) > CR total NC (2.87) > CR MC (2.22); the order of the correlation coefficients between the total NC, SAC, and respirable MC was R total NC and SAC (r = .681) > R SAC and total respirable MC (0.456) > R total NC and total respirable MC (0.424). These results were supported by our previous study [29][30][31]33 that examined the relationships among the NC, SAC, and MC of different nanoparticles in workplaces, and found that the total NC and SAC had a positive correlation (0.558-0.673), which were greater than the R SAC and MC or R NC and MC .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, the order of CR value at the location of slag releasing was: CR SAC (5.39) > CR total NC (2.87) > CR MC (2.22); the order of the correlation coefficients between the total NC, SAC, and respirable MC was R total NC and SAC (r = .681) > R SAC and total respirable MC (0.456) > R total NC and total respirable MC (0.424). These results were supported by our previous study [29][30][31]33 that examined the relationships among the NC, SAC, and MC of different nanoparticles in workplaces, and found that the total NC and SAC had a positive correlation (0.558-0.673), which were greater than the R SAC and MC or R NC and MC .…”
Section: Discussionsupporting
confidence: 82%
“…24 In addition, our previous field studies approved that the particle concentrations were significantly influenced by the sampling distance from sources, air velocity, background particles, and engineering control measures. [29][30][31] In this study, the personal NC was significantly higher than the total NC (Table 2), the reason might be that the personal NC was measured closer to the particle source. High wind velocity could enhance air exchange in the workshop, which was one of the main mechanisms for particle removal.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The correlation between total NC and SAC was 0.786, the correlation between NC and MC was 0.218, the correlation between SAC and MC was 0.380. The correlations between total NC, SAC, and MC has been explored in previous studies about ultrafine particles using real-time measurements 36 , 37 , which supported our finding. The high correlation between NC and SAC might be related to the fact that the 3007 counts the number of particles, the AeroTrak charges particles in a unipolar charge and then converting the number of particles into surface area.…”
Section: Discussionsupporting
confidence: 90%
“…Workers’ exposure to Al 2 O 3 NPs can mainly occur by inhalation. Occupational exposures to these dusts are described in the literature to have deleterious health effects on the respiratory and nervous systems [ 3 , 6 , 7 , 8 , 9 ]. Therefore, it is necessary to improve understanding of NPs toxicity in order to redesign strategies to mitigate/reduce environmental and/or health impact [ 10 ].…”
Section: Introductionmentioning
confidence: 99%